Evaluation of online teaching during the covid-19 pandemic in medical students: A case study in northern Iran - Aram Ghanavatizadeh; Ghahraman Mahmoudi; Mohammad-Ali Jahani (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: The COVID-19 pandemic has made universities of medical sciences face serious challenges as they are responsible for the preparation of the next generation of healthcare workers. The present study aimed to evaluate the online education of medical students during the COVID-19 pandemic, in Mazandaran province, Iran. Materials & Methods: This descriptive and analytical research was carried out from April 2022 to January 2023 in the universities of medical sciences in the Mazandaran province (Mazandaran University of Medical Sciences, Babol University of Medical Sciences, and Faculty of Medical Sciences of Islamic Azad University, Sari Branch). The participants were selected using the stratified random sampling method, and the sample size was calculated at 507 students. The required data was collected using a questionnaire and analyzed in SPSS software (version 21). It should be mentioned that a p-value of less than 0.05 was considered statistically significant. Results: The mean age of the students was 21.47 ± 2.34 years, with an age range of 18-43 years. Their mean scores in the dimensions of research, namely interacting, teaching, and learning, were 34.54±8.23, 53.93±10.15, and 33.8±8.01, respectively. The undergraduate students on average acquired 3.72, 1.25, and 1.00 more units of score in the three dimensions of interacting, teaching, and learning, respectively; however, this difference was only significant for the interaction dimension (P<0.001). The results showed that among the variables, the year of study and the level of education had a relationship with the total score (P<0.05) and were identified as independent and strong predictor variables for online education. Conclusion: Online education during the COVID-19 pandemic could become a suitable alternative to the traditional method of medical education. The most important factors that affect the quality of online education have been identified. Therefore, educational policymakers provide the required plans by considering the effective factors and attempt to improve the quality of online education by providing the necessary conditions and facilities.